Africanidades e educação popular: uma análise de propostas e vivências pedagógicas de movimentos negros em Sorocaba - Silva, Mariana Martha de Cerqueira (Universidade Federal de São Carlos, 2014)
This dissertation is about a survey that had the intention of reassuring the importance of approaching african and afro-brazilian history and culture in educational processes as from the dialogues between and with the black movement and relating brasilian´s africanidades to popular education perspective. Through the research action-participant methodology this work gathered and analysed interviews with local black leaderships that along with other historic sources provided our research material. Therefore, our group reserchead the contemporary black movement of Sorocaba city as well the educational experiences developed by them in the fifties of XX century. This survey was organized with the intention of revealing how by them could contribute to bring alive the application of Act 10.639/03.
Africanidades and popular education: the analysis of propositions and pedagogy experiences from black movements at Sorocaba
Keywords: Movimentos sociais; África - história; Educação popular; Movimento negro; Black movement; Popular education; Social movements; CIENCIAS HUMANAS::SOCIOLOGIA